El acceso a la justicia de las poblaciones indígenas. Una necesidad desde el lenguaje - Hurtado, Giovana (2024)
Indigenous peoples face limitations in understanding the justice system due to linguistic and cultural barriers; therefore, the use of clear and accessible language is essential for them to exercise their rights and participate effectively in judicial processes. Through a documentary review of the problems faced by indigenous peoples in accessing justice, the strategies developed by the Peruvian judiciary are described. It is stated that, despite the existence of regulations and policies that guarantee access to translators and interpreters in the judicial sphere, the actions are limited and need to be strengthened. There is a need for strategies that are sustained over time, and that allow their impact to be measured in order to evaluate their relevance and effectiveness. It is concluded that there is a need to develop a language policy focused on justice, which includes incentives —in the training of indigenous lawyers— as a mechanism for the preservation of indigenous languages. It also highlights the importance of language planning in the administration of justice in order to have native language-speaking operators in each judicial district, speciality and instance.